Решите уравнение (x-6) (x-3) ^3=(x+3) (x-6)…

Тема в разделе "Алгебра", создана пользователем Lex281, 17 окт 2019.

  1. Lex281

    Lex281 Мелюзга

    Регистрация:
    24 окт 2015
    Сообщения:
    0
    Симпатии:
    0
    Решите уравнение (x-6) (x-3) ^3=(x+3) (x-6) ^3
     
  2. Lubasha

    Lubasha Мелюзга

    Регистрация:
    9 фев 2013
    Сообщения:
    0
    Симпатии:
    0
    (x-6) (x-3) ^3=(x+3) (x-6) ^3x^4-15x^3+81x^2-189x+162-x^4+15x^3-54x^2-108x+648=081x^2-189x+162-54x^2-108x+648=027x^2-297x+810=0D=(-297) ^2-4*27*810=88209-87480=729x1=(27- (-297) / (2*27)=324/54=6x2=(-27- (-297) / (2*27)=270/54=5
     

Поделиться этой страницей